Mammographic density as a risk factor for breast cancer in a German case-control study - Heusinger, Katharina; Löhberg, Christian; Häberle, Lothar; Jud, Sebastian; Klingsiek, Peter; Hein, Alexander; Bayer, Christian M.; Rauh, Claudia; Uder, Michael; May, Matthias; Adamietz, Boris; Schulz-Wendtland, Rüdiger; et al. (European Journal of Cancer Prevention, 2011)
Mammographic percent density (MD) is recognized as one of the strongest risk factors associated with breast cancer. This matched case-control study investigated whether MD represents an independent risk factor. Mammograms were obtained from 1025 breast cancer patients and from 520 healthy controls. MD was measured using a quantitative computer-based threshold method (0-100%). Breast cancer patients had a higher MD than healthy controls (38 vs. 32%, P<0.01). MD was significantly higher in association with factors such as age over 60 years, body mass index (BMI) of 25-30 kg/m, nulliparity or low parity (one to two births). Average MD was inversely associated with age, BMI, parity and positively associated with age at first full-term pregnancy. MD was higher in women with at least one first-degree relative affected, but only among patients and not in the group of healthy controls (P<0.01/P=0.61). In women with an MD of 25% or more, the risk of breast cancer was doubled compared with women with an MD of less than 10% (odds ratio: 2.1; 95% confidence interval: 1.3-3.4; P<0.01); in the postmenopausal subgroup, the risk was nearly tripled (odds ratio: 2.7; 95% confidence interval: 1.6-4.7; P<0.001). This study provides further evidence that MD is an important risk factor for breast cancer. These results indicate strong associations between MD and the risk of breast cancer in a matched case-control study in Germany © 2010 Wolters Kluwer Health.
CRIS-Team Scopus Importer:2021-07-19